2019
DOI: 10.22211/cejem/109806
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl Terminated Polybutadiene: Chemical Modification and Application of these Modifiers in Propellants and Explosives

Abstract: Hydroxyl terminated polybutadiene (HTPB) as a telechelic liquid polymer has been widely used in propellants and explosives and many modified-HTPBs have been reported in the literature. As a binder or additive in propellants and explosives, the chemical modification of HTPB for improving certain properties of propellants has been summarized in detail in this article. According to the application drawbacks of HTPB, modified-HTPB can be classified differently. Furthermore, there are polymers that have been modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…There are no reports in the literature dealing with the modification of HTPB the same way as presented here, as far as these authors are aware. Recently reviews published by Cheng 2 and Zhang et al 43 showed several chemical modifications of HTPB, and the main purpose are to functionalize the polybutadiene in a way to increase its energetic output, to contribute for the specific impulse of propellants. However, all presented advantages and disadvantages, and none have been presented as a clear replacer for the pure HTPB.…”
Section: Cured Bindersmentioning
confidence: 99%
“…There are no reports in the literature dealing with the modification of HTPB the same way as presented here, as far as these authors are aware. Recently reviews published by Cheng 2 and Zhang et al 43 showed several chemical modifications of HTPB, and the main purpose are to functionalize the polybutadiene in a way to increase its energetic output, to contribute for the specific impulse of propellants. However, all presented advantages and disadvantages, and none have been presented as a clear replacer for the pure HTPB.…”
Section: Cured Bindersmentioning
confidence: 99%
“…Various attempts have been made to modify HTPB by hydrogenation, epoxidation, nitration, end terminal modification by amine, carboxyl, azido group etc in order to utilize the flexible nature of polybutadiene backbone for the above said applications [17–22] . HTPB is generally cured using polyisocyanates like toluene diisocyanate (TDI), hexamethylene diisocyanate (HMDI), isophorone diisocyanate (IPDI) etc to form polyurethanes (PU) [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts have been made to modify HTPB by hydrogenation, epoxidation, nitration, end terminal modification by amine, carboxyl, azido group etc in order to utilize the flexible nature of polybutadiene backbone for the above said applications. [17][18][19][20][21][22] HTPB is generally cured using polyisocyanates like toluene diisocyanate (TDI), hexamethylene diisocyanate (HMDI), isophorone diisocyanate (IPDI) etc to form polyurethanes (PU). [18] The corrosion resistance of polyurethane coatings on anodised magnesium substrates for aerospace applications were reported by Jothi et al [23] Polyurethane coating functionalised with hydroxypropylpolydimethyl siloxane was found to be an effective anti-cavitation coating for underwater over current components such as propellers, turbine blades etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although polyvinylpyridine derivatives and nitropolymers have found wide application as high-performance binders, over the years a number of polymers have been referred to as “energetic binders” ( Figure 1 ). The common structural features present in those systems include functionalisation (nitro-, nitrate- and azido- substituents are most commonly encountered) and replacement of the carbon atoms in the repeat units with oxygen or nitrogen atoms [ 8 ]. Among these polymers, particular research attention has recently been dedicated to polyoxetanes.…”
Section: Introductionmentioning
confidence: 99%